2002
DOI: 10.1002/app.10672
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polyindole by the incorporation of pyrrole unit

Abstract: Electrochemical copolymerization of pyrrole and indole was performed galvanostatically in a solvent of acetonitrile (AN)/water (vol %: 99/1). The product obtained was characterized by cyclic voltammetry and infrared spectroscopy. The influence of the monomer feed ratio of pyrrole and indole on the synthesis of the copolymer was investigated. The amount of pyrrole units in the copolymer chain increased with increase of the concentration of the pyrrole monomer in the solution. The results showed that the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…It is quite different from those of the copolymers, which further confirms the occurrence of copolymerization. 17 It is well known that PEDOT can be used as stable conducting material in tantalum capacitors owing to its pretty good redox properties. 25 According to Figure 3(e), a rapid increase in current density occurred during the process of potential scan followed by a plateau, while the reverse course showed discharge of stored charge as the capacitor returned to its original state, indicating a distinct capacitive feature of the charge storage.…”
Section: Electrochemistry Of Copolymer Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite different from those of the copolymers, which further confirms the occurrence of copolymerization. 17 It is well known that PEDOT can be used as stable conducting material in tantalum capacitors owing to its pretty good redox properties. 25 According to Figure 3(e), a rapid increase in current density occurred during the process of potential scan followed by a plateau, while the reverse course showed discharge of stored charge as the capacitor returned to its original state, indicating a distinct capacitive feature of the charge storage.…”
Section: Electrochemistry Of Copolymer Filmsmentioning
confidence: 99%
“…Similar to the electrocopolymerization of EDOT, copolymers obtained from Indole with different monomers have also been electrochemically synthesized. 12,16,17 By means of the electrochemical copolymerization, some new conducting polymers have been prepared with several obvious advantages, such as variation of conductivity, enhancement of electrochemical activity, and thermal stability. It is well known that the band gap of ICPs is a crucial factor to improve the properties of semiconductors, which is the difference in energy e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PIN has found usage in various areas; such as electronics, microwave absorbing materials, anode material in batteries, anticorrosion coatings, photovoltaics and supercapacitor applications [25][26][27][28]. In spite of the described advantages, PIN has comparatively been less studied in accordance to analogue conductive polymers, as indole monomer has low polymerization efficiency with chemical oxidants and poor mechanical properties due to its tendency on forming a powdery product [29,30]. But, a recent application has found usage of PIN as a fiber polymer electrode for lithium ion secondary battery [31].…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] Although some research groups have suggested that activated carbon/photocatalyst composites could be used as carriers to reuse nanoparticles, these composites prevent the irradiation of UV light to TiO 2 , and result in lower photocatalytic activity. 14,15 These template methods are complicated and may involve long process time. Among the promising candidate materials, hydrogels are attractive due to their highly absorbent properties, which are dependent on external environmental conditions, 9,10 and light-transparency in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%